1992
DOI: 10.1287/opre.40.4.804
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Demand Randomness on Inventories and Costs

Abstract: We explore analytically cardinal effects of the extent of demand randomness on optimal inventory levels and the associated expected costs. To model changes in demand randomness, we make extensive use of a mean-preserving transformation commonly used in probabilistic microeconomics, as well as the notion of risk-pooling (aggregating independent demands). For the single period (news vendor) model, the order quantity and associated costs are shown to depend on the randomness parameter in a simple and highly inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 16 publications
5
75
2
Order By: Relevance
“…Pasternack and Drezner (1991) show some interesting characteristics of optimal inventory levels in a two-product problem with full substitution. Gerchak and Mossman (1992) show that, contrary to intuition, substitution effects may result in an increase in optimal inventory levels under certain cost and demand conditions. The above papers consider single-period models where demands of the products are not correlated, unlike in our work.…”
Section: Literature Reviewcontrasting
confidence: 60%
“…Pasternack and Drezner (1991) show some interesting characteristics of optimal inventory levels in a two-product problem with full substitution. Gerchak and Mossman (1992) show that, contrary to intuition, substitution effects may result in an increase in optimal inventory levels under certain cost and demand conditions. The above papers consider single-period models where demands of the products are not correlated, unlike in our work.…”
Section: Literature Reviewcontrasting
confidence: 60%
“…Moreover, the optimal lot size, q * U , corresponding to G , is not the largest value of the production lot size amongst all convex-ordered yield-rate distributions. Note that the optimal lot sizes are known to be nonmonotone in demand variability (see Gerchak and Mossman 1992). However, the relationship between lot sizes and yield-rate variability appears not to have been studied before, except in the EOQ setting as described earlier.…”
Section: Insights and Examplesmentioning
confidence: 99%
“…For example, Gerchak and Mossman (1992) show that risk pooling, which occurs when several independent random demands are aggregated into one, can increase inventories or move order quantities further from mean or median demand in a single-echelon inventory system. Song (1994) shows that stochastically larger lead times may be associated with smaller long-run average cost.…”
Section: Introductionmentioning
confidence: 99%
“…Most of this research has focused on uncapacitated systems (exogenous lead times). Gerchak and Mossman [4] showed that, in a single-period newsvendor setting, the optimal replenishment quantity and the optimal cost are both increasing (under reasonable conditions) in the demand variability when demand is transformed using a mean-preserving transformation. Ridder et al [10] presented comparison results based on demand variability in the identical setting emphasizing at the same time that depending on the definition of variability, some counter-examples can be found.…”
Section: Introductionmentioning
confidence: 99%